Our castle by the sea - Strange, Lucy (Chicken House, 2019)
In WWII, eleven-year-old Petra (Pet) lives with her English father, German mother, and older sister in a small lighthouse cottage on England's southeast coast. Pet's mother is arrested and interned for national security purposes, which sparks an ever-unraveling series of secrets involving her sister's relationship with a local boy, Dunkirk, and charts and logbooks seized by the police. All throughout is blended an ancient legend of four girls who are turned to stone on top of the lighthouse's cliff top.